Lymphocyte networks are dynamic cellular communities in the immunoregulatory landscape of lung adenocarcinoma - Gaglia, Giorgio; Burger, Megan L; Ritch, Cecily C; Rammos, Danae; Dai, Yang; Crossland, Grace E; Tavana, Sara Z; Warchol, Simon; Jaeger, Alex M; Naranjo, Santiago; Coy, Shannon; Nirmal, Ajit J; et al. (Cancer cell, 2023)
Lymphocytes are key for immune surveillance of tumors, but our understanding of the spatial organization and physical interactions that facilitate lymphocyte anti-cancer functions is limited. We used multiplexed imaging, quantitative spatial analysis, and machine learning to create high-definition maps of lung tumors from a Kras/Trp53-mutant mouse model and human resections. Networks of interacting lymphocytes ("lymphonets") emerged as a distinctive feature of the anti-cancer immune response. Lymphonets nucleated from small T cell clusters and incorporated B cells with increasing size. CXCR3-mediated trafficking modulated lymphonet size and number, but T cell antigen expression directed intratumoral localization. Lymphonets preferentially harbored TCF1 PD-1 progenitor CD8 T cells involved in responses to immune checkpoint blockade (ICB) therapy. Upon treatment of mice with ICB or an antigen-targeted vaccine, lymphonets retained progenitor and gained cytotoxic CD8 T cell populations, likely via progenitor differentiation. These data show that lymphonets create a spatial environment supportive of CD8 T cell anti-tumor responses.